Effects of Banana Variety and Puffing Conditions on Puffed Banana Qualities - ทับเที่ยง, สุรพิชญ์; แท่นทอง, พิสุทธิ์ (Princess of Naradhiwas University Journal, 2018)
The high temperature and short time technique (HTST) was applied to various banana varieties for crisp banana producing. The HTST puffing suitable for producing of crisp banana because it can create high porous structure and more crisp texture as compared with hot air dried product. However, no previous literatures study the effect of banana variety on puffed product quality. Therefore, the objective of this experiment was to study the effect of banana variety (Namwa-banana and Homtong-banana) and puffing conditions (puffing temperature and puffing time) on puffed banana qualities i.e. colour, volume ratio and texture property. The Namwa-banana slices with 21-23 oBrix and Homtong-banana with 16-18 oBrix of total soluble solids were cut across into 2.5 min and it were blanched by 95 oC of hot water for 30 sec. After that, it were dried in 3 steps. First step, it were dried by hot air at temperature of 90 oC until its moisture content reached 35% dry basis (d.b.). Then, the slices were puffed by hot air (130, 150 and 170 oC) for a short duration (1.5, 2 and 2.5 min) in a laboratory HTST model. Final step, it were dried again by hot air at temperature of 90 oC until its moisture content reached 4% d.b. The experimental results showed that the banana variety affected on product quality. The puffed Namwa-banana had lower volume ratio and harder texture than puffed Homtong-banana. However, the puffed Namwa-banana had better colour quality than those puffed Homtong-banana. This is due to the Namwa-banana contains lower amount of monosaccharide than those ones. The puffing conditions, puffing temperature and puffing time, strongly affected on puffed banana quality. Increasing of puffing temperature together with longer puffing time provided higher volume ratio and more crisp texture. However, the color of product in both of banana varieties had more browning as higher puffing temperature and longer puffing time. To obtained a satistied puffed product, the banana should be puffed under puffing temperature of 150 oC at least 2 min of puffing time.